Hematological Manifestations of SLE at Initial Presentation: Is It Underestimated?. (9th July 2012) - Sasidharan, P. K.; Bindya, M.; Sajeeth Kumar, K. G.
Abstract : SLE can present with hematological manifestations alone or along with features of other system involvement. With a low index of clinical suspicion or inadequate follow up the diagnosis may be delayed or missed at the time of presentation, in those with hematological abnormalities as the initial manifestation. An observational study was conducted among patients of SLE, in a tertiary referral centre of North Kerala, with the purpose of estimating the proportion of patients with hematological manifestations as the initial presentation of the disease and to study their nature. It was observed that 82% of the patients had hematological manifestations at presentation. It is the most common presenting manifestation of SLE in people of North Kerala. Autoimmune hypothyroidism was one of the common coexisting abnormalities in these patients, which is not included in the American College of Rheumatology (ACR) criteria for diagnosis. Arthritis was uncommon among those who presented with hematological manifestations. A significant number of patients do not satisfy the ACR criteria at the time of diagnosis but do so on follow up. The ACR criteria are weak to diagnose such patients and therefore need revision. We therefore propose an alternative to ACR criteria as "Kozhikode criteria for SLE".